Urbanization and poverty in Maseru : a comparative study of Sekamaneng, Motimposo and Thibella. - Motsoene, Keneuoe A, (My University, 2014)
In the six decades since the mid 20th century, the world has experienced phenomenal urban growth, especially in the developing world. This growth has been closely associated with increasing levels of poverty and deprivation characterized by lack of access to safe water supplies, proper sanitation and access to assets. Other features include slums, informal settlements and low employment. This demographic shift is taking place within a context of low rates of economic growth and political engagement between the state and civil society. Lesotho, while sharing these experiences, is also one of the poorest countries in the world, ranking 158 out of 177 according to the UN Human Development Index. This has largely determined the nature of urbanization, with deepening economic problems in most of the country, rural and urban, resulting in poverty. Nevertheless, there has been a profound shift in location of that poverty. Whereas before it was overwhelmingly a rural phenomenon, now poverty is urbanized. In addition, due to the nature of urban development in the country, poverty is primarily concentrated in Maseru – the primary city of this small, land-locked country. While literature concentrates much on developing world cities, including those of Africa, it is silent on the impact of urbanization on poverty in Maseru. This thesis attempts to fill this gap and argues that rapid and differentiated forms of urbanization have increased poverty in Maseru. It studies how differentiated forms and patterns of urbanization have affected the manifestations of poverty in different parts of Maseru. It also analyses the different livelihood strategies employed by the poor residents of the three communities (Thibella, Sekamaneng and Motimposo) in Maseru as the increase in urbanization has unsettled conventional livelihood strategies, compelling them to employ different livelihood strategies to survive. Further, the study examines how the urban governance systems and people within them are coping with these pressures. The study concludes that the increased poverty in Maseru resulted from Lesotho and Maseru’s historic development trends, as the results confirm. However, urbanization significantly exacerbated this poverty. The varied processes of urban growth (inward migration and urban encroachment) have affected the manifestations of poverty and created different experiences of poverty in Maseru and, in turn, shaped the livelihood strategies of its inhabitants. The urban governance is failing to cope with the demands of this growth further increasing poverty.
Keywords: Urbanization--Lesotho--Maseru.; Poverty--Lesotho--Maseru.